WM in Adolescence: What Is the Relationship With Emotional Regulation and Behavioral Outcomes? - Malagoli, Chiara; Usai, Maria Carmen (Frontiers in Psychology, 2018)
Adolescence is a fundamental transition phase, marked by physical, social, cognitive and emotional changes. At this stage in development two contrasting phenomena take place: brain changes cause a sensitivity to emotional aspects (Dahl, 2004); while also control processes register as well impressive improvements (e.g. Best & Miller, 2010; Hooper et al., 2004). The study is aimed to investigate the relationship between a core cognitive feature such as working memory (WM) (Diamond, 2013) and complex abilities such as emotion regulation (ER) and behavioural self-reported outcomes using a structural equation model approach. A sample of 227 typically developed adolescents between 14 to 19 years of age (148 females; mean age in months 202.8, SD 18.57) participated in this study. The following tasks and self-reports were administered in a 45-minute test session at school: Symmetry Span task (Kane et al., 2004). Reading Span task (Daneman & Carpenter, 1980), Mr Cucumber (Case, 1985); Youth Self-Report (YSR, 11-18 years, Achenbach, 2001); Difficulties Emotion Regulation Scale (DERS, Gratz & Roemer, 2004; Italian version by Giromini et al., 2012). Results showed that difficulties in ER correlated with WM: high levels of ER difficulties are associated with low WM efficiency while no significant contributions of these predictors was observed on externalizing or internalizing symptoms. This study showed a significant relationship between self-reported difficulties in ER and WM, while no significant contribution of the considered predictors was showed on the outcomes, adding knowledge about how behavioural and emotional self-reported outcomes may relate to these processes.